2015
DOI: 10.1002/chem.201503591
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Molecular Memory Films Composed of Sequentially Assembled Heterolayers Containing Ruthenium Complexes

Abstract: Photoresponsive molecular memory films were fabricated by a layer-by-layer (LbL) assembling of two dinuclear Ru complexes with tetrapodal phosphonate anchors, containing either 2,3,5,6-tetra(2-pyridyl)pyrazine or 1,2,4,5-tetra(2-pyridyl)benzene as a bridging ligand (Ru-NP and Ru-CP, respectively), using zirconium phosphonate to link the layers. Various types of multilayer homo- and heterostructures were constructed. In the multilayer heterofilms such as ITO||(Ru-NP)m |(Ru-CP)n , the difference in redox potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…Recent studies have shown that polypyridyl ruthenium complexes with a Ru-C bond, namely cyclometalated ruthenium complexes, are particularly useful for the construction of molecular switches with multiple redox processes 21 22 . The presence of the Ru-C bond significantly decreases the Ru(III/II) potential and affords diruthenium 23 or ruthenium-amine 24 25 26 conjugated complexes with three redox states.…”
mentioning
confidence: 99%
“…Recent studies have shown that polypyridyl ruthenium complexes with a Ru-C bond, namely cyclometalated ruthenium complexes, are particularly useful for the construction of molecular switches with multiple redox processes 21 22 . The presence of the Ru-C bond significantly decreases the Ru(III/II) potential and affords diruthenium 23 or ruthenium-amine 24 25 26 conjugated complexes with three redox states.…”
mentioning
confidence: 99%
“…Therefore, the chloro complex reported here was initially prepared and isolated as an intermediate in the synthesis of binuclear precatalysts based on the {Ru(tppz)Ru} structural framework . In addition to catalysis, the bis-tridentate tppz ligand finds relevance to the assembly of donor-acceptor metal complexes with electron/ ISSN 2056-9890 energy-transfer properties for potential applications in molecular (opto)electronic devices (Davidson et al, 2015a;Fantacci et al, 2004;Nagashima et al, 2014Nagashima et al, , 2016Wadman et al, 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…1 The immobilization of such species on conducting surfaces has attracted great interest in the development of devices for applications dedicated to micro and nano electronics, biotechnologies, catalysis or solar energy conversion etc. [2][3][4][5] Within this context, ligands containing multiple metal-binding sites allow access to multicomponent arrays by combining different metal centers to give rich redox, optical or magnetic properties. Among the different possible chelating groups, bis (2,2':6',2"-terpyridine) derivatives are ideally suited for the construction of such well-defined metallo supramolecular assemblies on surfaces.…”
Section: Introductionmentioning
confidence: 99%